2004
DOI: 10.1007/s00239-004-2599-6
|View full text |Cite
|
Sign up to set email alerts
|

New Methods for Detecting Positive Selection at Single Amino Acid Sites

Abstract: Inferring positive selection at single amino acid sites is of particular importance for studying evolutionary mechanisms of a protein. For this purpose, Suzuki and Gojobori (1999) developed a method (SG method) for comparing the rates of synonymous and nonsynonymous substitutions at each codon site in a protein-coding nucleotide sequence, using ancestral codons at interior nodes of the phylogenetic tree as inferred by the maximum parsimony method. In the SG method, however, selective neutrality of nucleotide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 35 publications
1
44
1
Order By: Relevance
“…Therefore, κ was assumed to be 4 in the computation. For each codon site, the numbers of synonymous and nonsynonymous differences were summed and the numbers of synonymous and nonsynonymous sites were averaged with the weight proportional to the branch length over all branches of the phylogenetic tree, to obtain the total numbers of synonymous (c S ) and nonsynonymous (c N ) differences and the average numbers of synonymous (s S ) and nonsynonymous (s N ) sites (Suzuki and Gojobori, 1999;Suzuki, 2004a). Although multiple substitutions were not corrected in this method, the degree of underestimation for c S and c N appeared to be negligible for the data set analyzed in the present study, because the branch lengths were generally very small (Saitou, 1989).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, κ was assumed to be 4 in the computation. For each codon site, the numbers of synonymous and nonsynonymous differences were summed and the numbers of synonymous and nonsynonymous sites were averaged with the weight proportional to the branch length over all branches of the phylogenetic tree, to obtain the total numbers of synonymous (c S ) and nonsynonymous (c N ) differences and the average numbers of synonymous (s S ) and nonsynonymous (s N ) sites (Suzuki and Gojobori, 1999;Suzuki, 2004a). Although multiple substitutions were not corrected in this method, the degree of underestimation for c S and c N appeared to be negligible for the data set analyzed in the present study, because the branch lengths were generally very small (Saitou, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Although the single-substitution analysis is conceptually different from the single-site analysis, they are methodologically similar to each other. It has been shown that the latter analysis is generally conservative and reliable in the computer simulation and real data analysis (Suzuki and Gojobori, 1999;Suzuki, 2004aSuzuki, , 2007. It should be noted that in the single-substitution analysis, positive selection for original substitutions can be detected even when the number of (reverse) nonsynonymous substitutions is 0.…”
Section: Single-substitution Analysis Of Natural Selectionmentioning
confidence: 99%
“…Therefore, if balancing selection favours diversity at the PBR of MHC genes, advantageous nonsynonymous mutations will be retained and a high ratio of nonsynonymous to synonymous substitutions will be observed. Tests of deviation of dN:dS from parity are becoming increasingly sophisticated (Nielsen, 1997;Bierne and Eyre-Walker, 2003), and can now explicitly examine which amino-acid sites show the most potent signatures of selection (Nielsen and Yang, 1998;Suzuki, 2004;Massingham and Goldman, 2005). Such approaches will prove useful in studies of the MHC, as the effects of selection on specific peptide-binding codons can be ascertained.…”
Section: Detecting Selection In Contemporary Populationsmentioning
confidence: 99%
“…Many variations of this class of test exist. They differ in the amount of sequence data and computational resources required (Suzuki and Gojobori 1999;Suzuki 2004;Massingham and Goldman 2005;Pond and Frost 2005;Zhang et al 2005). The second class of tests relies on predictions made by the neutral theory for allele or haplotype frequencies (Kreitman 2000;Bamshad and Wooding 2003) within and among populations.…”
mentioning
confidence: 99%